EVALUASI IMPLEMENTASI PROGRAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR MENGGUNAKAN CIPP - Suryadi, Fransisca Liliana Pranita; Wardani, Krisma Widi (Universitas Negeri Medan, 2024)
The Character Education Programme is a national development priority program to realize the mandate of the 1945 Constitution. According to Stufflebeam, this research is an evaluative research using a descriptive qualitative approach with the CIPP model. The data were obtained through questionnaires, interviews, and document studies with the subjects of students, principals, teachers, and parents of students of SD Kanisius Cungkup Salatiga. This research aims to determine the implementation of the Character Education Programme in SD Kanisius Cungkup Salatiga based on context, input, process, and product. The results showed that the context aspect includes the vision and mission, the 5 fundamentals of Kanisius, and the 5 character values of PPK as the program's foundation. The input aspect provides program planning and supporting resources. The process aspect consists of program implementation, the role of the principal, and teachers. The product aspect consists of goal achievement, results, and program sustainability. It is found that The Character Education Programme at SD Kanisius Cungkup Salatiga can develop students' character. This can be seen from the religious aspect and the nationalist element has developed, the integrity aspect has been cultivated, the independent aspect and the cooperation aspect have developed.